PENGARUH CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING LOAN (NPL), BIAYA OPERASIONAL PADA PENDAPATAN OPERASIONAL (BOPO), LOAN TO DEPOSIT RATIO (LDR) TERHADAP RETURN ON ASSET (ROA) Pada Bank BUMN Periode 2013 - 2017 - Indraswari, Arinah; Kardiaty, Endah Nurhawaeny (Prodi Akuntansi, Fakultas Ekonomi, Universitas Muhammadiyah Cirebon, 2017)
This research has a purposed to provide empirical evidences about the CapitalAdequacy Ratio (CAR), Nonperforming Loans (NPL) , Operating Expenses to Operating Income(BOPO), Loan to Deposit Ratio (LDR) towards profitability (ROA) on state owned bank. Timeperiod uses in this research begin from 2013 until 2017. The analyzed method in this research usesmultiple linear regressions including classical assumption such as normality test, multicolinearitytest, heterocedacity test, and autocorrelation test. The result shown that Operating Expenses toOperating Income (BOPO) variables have positive relation and significantly influence towardsROA. Meanwhile Capital Adequacy Ratio (CAR), Nonperforming Loans (NPL) , Loan to DepositRatio (LDR) have negative relation and significantly influence towards ROA.Keywords: Capital Adequacy Ratio (CAR), Nonperforming Loans (NPL) , Operating Expensesto Operating Income (BOPO), Loan to Deposit Ratio (LDR) and Profitability